Parenting Style and Religious Character: The Mediating Role of Worship Discipline - Mushlih, Aguslani (EduBase : Journal of Basic Education, 2025)
This study investigates the influence of parenting styles on students’ religious character, with worship discipline as a mediating factor. It addresses a research gap by integrating parenting and religious habituation into a single model of character formation. Using a quantitative approach with correlational-verification design, the study surveyed 200 junior high school students in Cianjur, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that parenting style has a significant effect on both worship discipline and religious character, with worship discipline acting as a partial mediator. The model demonstrates good fit and predictive relevance (Q² > 0.5), highlighting the crucial role of family-based religious routines. These findings suggest that religious character can be strengthened through consistent parental involvement and structured spiritual practices at home. The study offers a novel empirical contribution by positioning worship discipline as a behavioral bridge between parenting and religious values in youth development.